1976
DOI: 10.1007/bf00692778
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of benzodiazepines with neuroleptics at central dopamine neurons

Abstract: Several benzodiazepines (chlordiazepoxide, clonazepam, diazepam and flunitrazepam) markedly counteracted the elevation of the homovanillic acid (HVA) content of the rat brain induced by neuroleptics (haloperidol, pimozide, chlorpromazine, and clozapine). A similar effect was obtained with the inhibitor of GABA transaminase, aminooxyacetic acid (AOAA). The interaction of benzodiazepines with the neuroleptic-induced HVA increase was similar in the striatum and in the limbic forebrain and was antagonized by the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Besides dopamine, several neurotransmitters like serotonin, acetylcholine, GABA or endorphins are found to be involved in the expression of catalepsy and haloperidol-induced catalepsy can be blocked by such diverse drugs as selective dopamine D 3 receptor antagonists [45], 5-HT 1A agonists [46,47], anti-cholinergics [48] or A 2A receptor antagonists [49]. There are also well-known interactions between the GABAergic and dopaminergic system [50,51] and classic benzodiazepines like diazepam potentiate haloperidol-induced catalepsy [52]. On the contrary, GABA A agonists like muscimol are reported to antagonise haloperidol-induced catalepsy at low doses with reverse effects at higher doses [53] and, interestingly enough, GABA B agonist baclofen antagonises the action of haloperidol in a low dose (1 mg/kg) without any visible effect in higher doses (2-8 mg/kg) [54].…”
Section: Discussionmentioning
confidence: 99%
“…Besides dopamine, several neurotransmitters like serotonin, acetylcholine, GABA or endorphins are found to be involved in the expression of catalepsy and haloperidol-induced catalepsy can be blocked by such diverse drugs as selective dopamine D 3 receptor antagonists [45], 5-HT 1A agonists [46,47], anti-cholinergics [48] or A 2A receptor antagonists [49]. There are also well-known interactions between the GABAergic and dopaminergic system [50,51] and classic benzodiazepines like diazepam potentiate haloperidol-induced catalepsy [52]. On the contrary, GABA A agonists like muscimol are reported to antagonise haloperidol-induced catalepsy at low doses with reverse effects at higher doses [53] and, interestingly enough, GABA B agonist baclofen antagonises the action of haloperidol in a low dose (1 mg/kg) without any visible effect in higher doses (2-8 mg/kg) [54].…”
Section: Discussionmentioning
confidence: 99%
“…Since a GABA-ergic system has been proposed, that exerts an inhibitory effect on the nigro-striatal dopaminergic system (Kim et al, 1971), a potentiation of GABA-ergic transmission by either structural analogues or by elevation of endogenous brain GABA levels would be expected to increase the cataleptogenic effect of neuroleptics. Keller, Schaffner & Haefely (1976) proposed a similar mechanism and reported that amino-oxyacetic acid which elevates brain GABA levels by inhibiting the enzyme GABAtransaminase (Collins, 1973) and benzodiazepines which have been reported to facilitate GABA-ergic transmission (Haefely, Kulcsar, Mohler, Pieri, Polc & Schaffner 1975), potentiated the cataleptogenic effect of haloperidol.…”
Section: Resultsmentioning
confidence: 95%
“…The potentiation of neuroleptic-induced catalepsy by GABA-mimetic drugs has been related to the latter's enhancement of GABA-ergic inhibition of the ascending nigro-striatal dopaminergic pathway (Keller et al, 1976). The striato-nigral GABA-ergic input to the substantia nigra is primarily considered to exert an inhibitory effect upon the ascending nigro-striatal dopaminergic pathway (Yoshida & Precht, 1971; Gale & Guidotti, 1976), although more recent studies have implicated a more complex and diverse involvement (Dray, Fowler, Oakley, Simmonds & Tanner, 1977;Cheramy et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of drugs with proposed y-aminobutyric acid (GABA)-ergic agonist activity to potentiate neuroleptic-induced catalepsy has been attributed to the enhanced GABA-ergic inhibition of the ascending nigrostriatal dopaminergic pathway (Kaariainen, 1976;Keller, Schaffner & Haefely, 1976;Worms, Willigens & Lloyd, 1978). Evidence for the inhibitory regulation of this dopaminergic pathway by a descending striato-nigral GABA-ergic pathway has been obtained electrophysiologically (Crossman, Walker & Woodruff, 1974), behaviourally (Tarsy, Pycock, Meldrum & Marsden, 1975) and pharmacologically (Cheramy, Nieoullion & Glowinski, 1978).…”
Section: Introductionmentioning
confidence: 99%